2021
DOI: 10.3389/fbioe.2021.587082
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Enhanced Mechanistic Simulation Framework for Functional Deficit Prediction in TBI

Abstract: Resting state functional magnetic resonance imaging (rsfMRI), and the underlying brain networks identified with it, have recently appeared as a promising avenue for the evaluation of functional deficits without the need for active patient participation. We hypothesize here that such alteration can be inferred from tissue damage within the network. From an engineering perspective, the numerical prediction of tissue mechanical damage following an impact remains computationally expensive. To this end, we propose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…This study indicated sML could be used to predict the necessity of a head CT regarding childhood mTBI. Although AI-based systems are powerful technologies [44][45][46][47][48][49][50][51], they should not replace the clinical judgment of physicians and medical teams [29][30][31][32][33]. The ideal role of these systems is as a data-driven input to the surgical decision-making process, designed to solve focused problems such as predicting the risk of mTBI in this study.…”
Section: Plos Onementioning
confidence: 99%
“…This study indicated sML could be used to predict the necessity of a head CT regarding childhood mTBI. Although AI-based systems are powerful technologies [44][45][46][47][48][49][50][51], they should not replace the clinical judgment of physicians and medical teams [29][30][31][32][33]. The ideal role of these systems is as a data-driven input to the surgical decision-making process, designed to solve focused problems such as predicting the risk of mTBI in this study.…”
Section: Plos Onementioning
confidence: 99%
“…The development and implementation of supervised machine learning (ML)-based surrogates of complex biomechanics models is relatively recent. Promising applications of the ML surrogates include parameter estimation and uncertainty quantification problems across several fields, such as TBI (Cai et al, 2018;Wu et al, 2019;Ghazi et al, 2021;Schroder et al, 2021;Zhan et al, 2021), cardiovascular (Davies et al, 2019;Cai et al, 2021) and musculoskeletal biomechanics (Pal et al, 2008;Strickland et al, 2010;Bartsoen et al, 2021). Regarding the research on head impact biomechanics, Wu et al (2019), Ghazi et al (2021), Zhan et al (2021) employed machine learning algorithms to predict the brain strain response of computationally expensive FE models of the human head in an accurate and time-efficient way.…”
Section: Introductionmentioning
confidence: 99%